Tenfold increase in cassava yields? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Tenfold increase in cassava yields? The quantity of tubers produced by cassava is roughly proportional to the amount of photosynthesis taking place in the aerial part of the plant. It follows that to increase yields of tubers, the ratio of the part...